Application of Neurocomputer Interfaces for Rehabilitation of Patients With Disorders of Motor Functions of the Nervous System - Duhaidahawi Murtadha Ahmed Luti; Dheyab Salman Ibrahim; Mohammed Shakir Mahmood; Omar Dawood Mohammed Al-Tai; Al-Karawi Raad Joudat Salman (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Brain-computer interface (BCI) technology allows a person to learn to control external actuators by means of arbitrary modification of their own EEG directly from the brain without involving nerves and muscles in this process, allowing to control external technical systems directly by brain signals. In the last two decades, BCI technology has been rapidly developing: its areas of application are expanding, new types of sensors for recording brain signals are being proposed, the quality of their recognition is improving, and methods for training subjects to control BCI are being perfected. At the beginning, the main goal of BCI development was to replace or restore motor functions of a person suffering from neuromuscular disorders. Currently, the tasks of BCI development have significantly expanded, increasingly capturing various spheres of life of a healthy person.